Memorandum on the situation in Asturias
011-0036-002 Confidential Memorandum on the Situation in Asturias (1) Fear of the terrible slaughter which will be the fate of the Asturian miners if they surrender, is unfortunately more than justified when one recalls the fact that since 1934 the mining population of Asturias has been an especial object of hatred, of the military elements in particular. There can be no doubt that the 1934 suppression would be reproduced in horror a hundred-fold; more even, for the possibility of escape, which existed for many in 1934, is to-day out of the question. It is quite certain that the surrender of Asturias means the death of many thousands of its heroic defenders, and first and foremost of the handful of men whose administrative and organising activities place them on a preferent plane. It is not a question of extremists. The whole Asturian Miners' organisation is characterized by its moderation and constructive outlook, and it was these qualities which gave the Mining Union of Asturias its tremendous moral and material strength. (2) It is now a question of saving the lives of a working population who have, in spite of themselves, been converted by the rebellion into shock troops ; and of their families and leaders. Apart from its humanitarian interest, this work has a political value of very great importance. By saving the lives of these people, the moderate and constructive tendency among; the Trades Unions and the Socialist Party, who to-day have a decisive influence in the Republican Government, would be considerably reinforced, especially through the incorporation of the leaders in the frame-work of those organisations which constitute one of the principal supports of the Republican regime. In the second place, such action would prevent the tremendous outcry and indignation which would be aroused in the Spanish liberal conscience by the cold-blooded and useless sacrifice of these men, who are generally recognised as representing one of the strongest 292/946/11/36(ii)